Managing change to implement integrated urban water management in African cities - Bahri, A.; Brikke, F.; Vairavamoorthy, Kalanithy (Elsevier, 2016)
With increasing pressures from global changes (urbanization, climate change, etc.), cities in Africa will experience difficulties in efficiently managing water resources. Most of the urbanization in Africa over the next 30 years will occur in fast-growing small towns that lack mature infrastructure. This offers a unique opportunity to implement innovative solutions based on integrated urban water management (IUWM). While IUWM approaches have been widely reported in the literature, their application has been limited. This paper describes the African Water Facility’s experience in applying the approach to three projects, in the Seychelles, Zimbabwe and Democratic Republic of Congo, which illustrate the types of challenges faced in different institutional frameworks and contexts (such as islands, a small town and a megacity). The paper identifies the critical issues for improving uptake and scaling up, including strong leadership, the commitment of government and the institutions involved, and a formal programme of capacity building and technical assistance.